Aspectos da biologia, da detecção de resistência e associações de herbicidas visando ao controle de Digitaria insularis resistente ao glyphosate - Gemelli, Alexandre (2013)
The resistance of Digitaria insularis to glyphosate is a worrying fact for Brazilian agriculture, because this perennial and rhizomatous weed can develop and flowering throughout the year in the climatic conditions of most agricultural regions of Brazil. This work aimed to study some aspects of biology, detection of resistance and herbicide associations for the control of Digitaria insularis resistant to glyphosate. It was found that the method for detection of D. insularis resistance via germination test with glyphosate solution is feasible only with qualitative test. The air temperature in Maringá-PR throughout the year was not a limiting factor for germination of sourgrass. Among the herbicide associations evaluated, some combinations with a formulation of glyphosate and ACCase inhibitor and an inhibitor of ALS showed good results in controlling D. insularis resistant to glyphosate. However, in advanced stages of development of this weed, the problems of antagonism in mixtures emphasized. Only a few combinations showed satisfactory results and stability at all stages evaluated.